IOT Based DC Motor Speed and Direction Control (International Journal of Scientific Research in Science and Technology, 2024)
This paper introduces an innovative Internet of Things (IoT) based system designed to control the speed and direction of a DC motor using the Blynk mobile application. The system integrates an OLED display (SSD1306), an ESP8266 microcontroller, a 300 RPM DC motor, and an L293D motor driver. With this system, users can remotely manage the speed and direction of the DC motor through the Blynk app, accessible on smartphones or tablets. Real-time feedback on the motor’s speed and direction is provided via the OLED display, enhancing user interaction and experience. The ESP8266 microcontroller acts as the core control unit, interfacing with the Blynk app via Wi-Fi to receive user commands and adjust the motor’s operation accordingly. The bidirectional control feature of the L293D motor driver enables precise manipulation of the motor’s speed and direction. By leveraging IoT technology and the Blynk app, users gain the flexibility to control the motor from any location with internet connectivity, offering convenience and accessibility. Additionally, the OLED display enhances the user interface, enabling intuitive monitoring and adjustment of motor parameters. In conclusion, this system offers a versatile and user-friendly solution for remotely managing DC motor speed and direction, with potential applications spanning across home automation, robotics, and industrial control systems.